CircFAM114A2 Promotes Cisplatin Sensitivity via miR-222-3p/P27 and miR-146a-5p/P21 Cascades in Urothelial Carcinoma - Lv, Jiancheng; Zhou, Zijian; Wang, Jingzi; Yang, Xiao; Yu, Hao; Han, Jie; Feng, Dexiang; Yuan, Baorui; Wu, Qikai; Li, Pengchao; Lu, Qiang; Yang, Haiwei (Frontiers in Oncology, 2021)
Introduction: Circular RNAs (circRNAs) are noncoding RNAs that have the structure of a covalently closed loop. Increasing data has proved that circRNAs can influence the progression and chemotherapy sensitivity of tumors. Therefore, the underlying function and mechanisms of more circRNAs in progression and chemotherapy resistance are important. Methods: We conducted RNA-sequencing on 5 pairs of urothelium carcinoma samples and screened for circRNAs. CircFAM114A2 was found to be low expressed in urothelium carcinoma. The functions of circFAM114A2 in urothelium carcinoma were explored using cell cycle assay, IC50 determination, cell proliferation assay, apoptosis assay and tumorigenesis assays in nude mice. Results: We discovered that circFAM114A2 levels were decreased in urothelium carcinoma cell lines and tissues. According to follow-up data, urothelium carcinoma patients with higher circFAM114A2 expression had better survival. Importantly, the levels of circFAM114A2 were associated with the histological grade of urothelium carcinoma. CircFAM114A2 could inhibit cell proliferation and block more urothelium carcinoma cells in G1 phase, and then increased sensitivity of urothelium carcinoma to cisplatin chemotherapy. Mechanistically, circFAM114A2 directly sponged miR-222-3p/miR-146a-5p and subsequently influenced the expression of the downstream target genes P27/P21, which, in turn, inhibited progression of urothelium carcinoma and increased cancer cells sensitivity to cisplatin chemotherapy. Conclusion: CircFAM114A2 could inhibit progression and promote cisplatin sensitivity in urothelium carcinoma through novel circFAM114A2/miR-222-3p/P27 and circFAM114A2/miR-146a-5p/P21 pathways. CircFAM1142 has therefore great potential as a prognostic biomarker and therapeutic target for urothelium carcinoma.